Assessment of increasing loading rate on two-stage digestion of food waste. (February 2016) - Voelklein, M.A.; Jacob, A.; O' Shea, R.; Murphy, J.D.
Highlights: Single and two-stage digestion of food waste was compared at increased loading. The methane content of the biogas increased by 14% to 71% in the two-stage system. The two-stage system yielded up to 23% more methane than the single-stage system. The two-stage system produced up to 404 L CH4 kg −1 VS or 15.1 MJ kg VS −1 . Abstract: A two-stage food waste digestion system involved a first stage hydrolysis reactor followed by a second stage methanogenic reactor. Organic loading rates (OLR) were increased from 6 to 15 g VS L −1 d −1 in the hydrolysis reactor and from 2 to 5 g VS L −1 d −1 in the methanogenic reactor. The retention time was fixed at 4 days (hydrolysis reactor) and 12 days (methane reactor). A single-stage digester was subjected to similar loading rates as the methanogenic reactor at 16 days retention. Increased OLR resulted in higher quantities of liquid fermentation products from the first stage hydrolysis reactor. Solubilisation of chemical oxygen demand peaked at 47% at the maximum loading. However, enhanced hydrolysis yields had no significant impact on the specific methane yields. The two-stage system increased methane yields up to 23% and enriched methane content by an average of 14% to levels of 71%.